Overcompensation of ecosystem productivity following sustained extreme drought in a semiarid grassland. Issue 4 (6th March 2023) - Ru, Jingyi; Wan, Shiqiang; Hui, Dafeng; Song, Jian
Abstract: Drought events are projected to be more extreme and frequent in the future and have profound influences on the structure and functions of terrestrial ecosystems. Thus, better understanding the mechanisms of recovery is critical for predicting the future dynamics of terrestrial ecosystems. We performed a 7‐year field precipitation experiment to examine recovery of a grassland ecosystem from different magnitudes of sustained drought, from slight to extreme. The ecosystem was exposed to precipitation treatments in the first 3 years (2010–2012) and recovered during the last 4 years (2013–2016) without precipitation treatments. Overall, large reductions of aboveground net primary productivity (ANPP, −43.3%) and perennial forb biomass (−83.1%) were observed in the third year (2012) of extreme drought only. Nevertheless, ANPP fully recovered within 1 year after the drought treatments were terminated, and the rapid recovery was mainly due to increased soil total nitrogen and root biomass allocation after drought. Surprisingly, large increases of ANPP under the extreme drought treatment occurred during the recovery periods from 2013 to 2015 (+74.1, +88.5, and +119.8 g m −2 year −1 ) compared to the control. The overcompensation offset the extreme drought‐induced reduction of ANPP in the treatment years and was primarily ascribed to the enhanced biomass of perennial grasses (PG). Higher resistance to drought and fast resource acquisition strategy might drive the rapid recovery and expansion of PG. Our findings revealed the rapid recovery of grasslands and the critical role of community overcompensation in maintaining grassland ecosystem function and stability under future climate change scenarios.